Measuring the Amount of AFM1 in Milk in Isfahan Province - Iraj Javadi (Journal of Global Pharma Technology, 2017)
A Flatoxin (AF) is a toxic metabolite produced by fungi of Aspergillus flavus, Aspergillus Parasiticus and Aspergillus Nomius. Among them, AFB1 is the most toxic and potent agent. AFM1 and AFB1 are metabolites primarily produced by AFB2 and AFM2 which are found mostly in milk and meat from animals have been fed by AF-contaminated foods. Given the risks of AF for men and also due to the high consumption of milk and dairy products, the aim of this project is to examine the contamination of the food by measuring the toxin in milk in Isfahan province and compare it with international standards as well as take steps to reduce and prevent the contamination. In this study, a number of raw milk samples from a milk station, Shahreza dairy store, Isfahan diary and Pegah Milk factory of Isfahan were collected to measure AFM1. To measure AF in milk, AFM1 was extracted with chloroform and column chromatography on a silica gel 60 G with anhydrous sodium sulfate were used for purification. AFM1 was detected and measured using two methods; 1- TLC with silica stationary phase and mobile phase chloroform - acetone - isopropanol in a ratio of (87 + 3 + 10), 2- using C18 reverse-phase HPLC with columns and methanol - acetonitrile water mobile phase in ratios (15:22:63) and UV detector at 350 nm. The results showed that 20% of the total samples collected from Shahreza milk station is contaminated with AFM1. Also, in 25% of samples taken from Shahreza dairy store, AFM1 was detected. The average amount of AFM1 in samples collected from Shahreza milk station and Shahreza dairy store was obtained 1.9 ± 0.26 and 2.9 ± 0. 59 ppb, respectively. In all the samples that the toxin has been detected in them, AFM1 was much higher than the limit set. However, in the samples prepared from Najaf Abad, Tiran and Karvan and Shahin Shahr, AFM1 was below the acceptable level. According to results, high content of AFM1 in the raw milk is worrying and more attention should be paid to control and monitor the milk production and consumption.Keywords: Aflatoxin, Raw milk, Isfahan province.